THE THE DIFFERENCE EFFECTIVENESS OF THE INTERVAL EXERCISE AND FARTLEK EXCERCISE IN IMPROVING CARDIOVASCULAR ENDURANCE IN BASKETBALL PLAYERS AGE 16-17 YEARS - Mahardana, I Gusti Ngurah Agus Putra; Winaya, Niko; Wahyuni, Nila (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Cardiovascular endurance is the ability to perform an activity with a long time without experiencing fatigue.The purpose of this research is to know the effect of the increase in the interval exercise and fartlek exercise in improving cardiovascular endurance.This research is experimental research using the design of Pre and Post Test Two Group Design.Sample research totalling 28 people are divided into two groups, Group 1 given interval excercise, fartlek excercise given group 2. Test of normality and its homogeneity of data is tested by using the Shapiro-Wilk Test and Levene's Test. The result showed an increase in cardiovascular endurance in group 1 and group 2. Paired sampel t - tes results-test obtainde a significant difference with the value p=0,000 (p<0,05) in group 1 and the value of p=0,000 (p<0,05) on group 2. Independent t-test showed no meaningful difference betwween group 1 and group 2 where p=0,863 (p>0,05). Based on the result of the study it can be concluded that there was no difference in effectiveness between interval excercise and fartlek excercise in improving cardiovascular endurance. Keywords:cardiovascular endurance, interval exercise, fartlek exercise.